Representation and Inclusion in School Councils in Mozambique - Taela, Kátia; López Franco, Erika; Alex, Shankland; Maivasse, Catija; Chilengue, Nárcya; Goodfry, Claudino (Institute of Development Studies, 2018)
This study was conducted as part of the Citizen Engagement Programme (Programa Cidadania e Participação (CEP)) in Mozambique – an empowerment and social accountability initiative to improve the quality of education and health services by increasing citizens’ influence on the management of schools and health units, the formulation of education and health policies, and the provision of education and health services. In education, CEP enabled citizen monitoring of services through the community scorecard (Cartão de Pontuação Comunitária (CPC)), focusing on the link between CPC action plans and the work plans of the co-management mechanism in schools – the school councils. CEP has also promoted the channelling of issues beyond the capacity and mandate of schools to higher levels of the national education system. This work identified a need to better understand the role of school councils as a link between the school and the community, and also in escalating important matters to higher levels of management in the education system, beyond that of school authorities. It was in this context that the Institute of Development Studies and the Centre for Learning and Capacity Building for Civil Society, both members of the CEP consortium, proposed to undertake a qualitative study on representation and inclusion in school councils. The primary aim of this study was to widen the knowledge base available to civil society and to government on the factors that contribute to good performance by school councils in building inclusivity and social accountability to improve the quality of education services.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; Important; L - english / inglês; M - ethnography / etnografia; access to services / acesso a serviços; citizenship & participation / cidadania e participação; civil society / sociedade civil; decentralization / descentralização; education / educação; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Barómetro Municipal 2017. Relatório de dados quantitativos. - IESE (Instituto de Estudos Sociais e Económicos (IESE), 2018)
É o novo relatório de pesquisa produzido por uma equipa de investigadores do Instituto de Estudos Sociais e Económico (IESE), coordenada por Salvador Forquilha, no quadro de um projecto de investigação em curso sobre a avaliação dos munícipes em relação ao desempenho da governação municipal em Moçambique. Este primeiro “Barómetro da Governação Municipal 2017” (BGM) explora dados quantitativos relativos à percepção dos munícipes sobre as diferentes vertentes da actuação dos órgãos e serviços municipais e que podem permitir às autoridades municipais melhor conceberem os seus planos de governação e a responderem de maneira mais eficaz às expectativas dos munícipes. Refira-se que nesta primeira fase do projecto BGM foram abrangidos oito municípios, cobrindo diferentes regiões do país, nomeadamente Beira, Ilha de Moçambique, Lichinga, Manjacaze, Nampula, Pemba, Quelimane e Tete.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; governance / governação

How do gender relations affect the working lives of close to community health service providers? Empirical research, a review and conceptual framework - Steege, Rosalind; Taegtmeyer, Miriam; McCollum, Rosalind; Hawkins, Kate; Ormel, Hermen; Kok, Maryse; Rashid, Sabina; Otiso, Lilian; Sidat, Mohsin; Chikaphupha, Kingsley; Datiko, Daniel Gemechu; Ahmed, Rukhsana; et al. (Social Science & Medicine, 2018)
Close-to-community (CTC) providers have been identiﬁed as a key cadre to progress universal health coverage and address inequities in health service provision due to their embedded position within communities. CTC providers both work within, and are subject to, the gender norms at community level but may also have the potential to alter them. This paper synthesises current evidence on gender and CTC providers and the services they deliver.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde